Complexifying quality: educator examples - Grieshaber, Susan; Hunkin, Elise (Frontiers in Education, 2023)
Quality in early childhood education settings has dominated the global economic policy agenda since the early 1990s, and despite decades of public investment, quality reform has stalled in Australia and internationally. This lack of quality improvement has been attributed to the inadequacy of the standardised, quantitative, and economic perspectives that drive policy, which are increasingly focused on systematised, academic interpretations of quality. The most impactful dimensions of quality are interpersonal and include warm, frequent interactions and rich, responsive play-based environments (OECD, 2018). However, little is known about these dimensions of quality and research is urgently needed. This paper reports initial data from a small-scale project investigating educator- and pre-service teacher-participant responses to prompts from researchers about what constitutes quality, including ‘in the moment’ experiences. Participants posted responses to researcher prompts to an online platform. Educator and pre-service teacher perspectives about their experiences of what constitutes quality provide a novel alternative to dominant discourses. Identifying some of the more complex dimensions of quality from the experiences of educators and pre-service teachers may reveal insight into previously untapped and difficult to access tacit knowledge.